Preparation method and application of tungsten disulfide / graphene composite material
By depositing tungsten salt on graphene oxide-modified silicon spheres and carrying out high-temperature vulcanization reaction, tungsten disulfide/graphene composite material was prepared, which solved the problem of tungsten disulfide structural collapse and poor conductivity, and achieved electrochemical materials with high sodium storage ability and cycle stability.
Patent Information
- Application Number
- CN202311344909.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-17
AI Technical Summary
As the negative electrode material of sodium ion batteries, tungsten disulfide has a layered structure and poor conductivity that lead to structural collapse and insufficient sodium storage capacity, and poor long-term cycle stability.
By depositing the tungsten salt on the surface of graphene oxide-modified silicon spheres, passing high-temperature vulcanization reaction, and undergoing alkali and acid treatment, a tungsten disulfide/graphene composite material with a three-dimensional multi-stage pore structure was prepared.
The composite material exhibits excellent electrochemical properties in sodium ion batteries, including improved sodium storage capacity and enhanced cycle stability, and has a simple process and a wide range of applications.
Smart Images

Figure CN119841352A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical materials, and in particular to a preparation method and application of a tungsten disulfide / graphene composite material. Background Art
[0002] As one of the most promising negative electrode materials for sodium ion batteries, tungsten disulfide has a unique layered structure and a high theoretical specific capacity (432 mAh g -1 ) and has attracted extensive attention from researchers (Chemical Communications.50.4192(2014)). However, the layered tungsten disulfide nanosheets are bound together by weak van der Waals forces, and the nanosheets are prone to folding and stacking during the continuous charging and discharging process, resulting in structural collapse, which in turn affects the performance of the battery. At the same time, the poor conductivity of tungsten disulfide is also one of the main factors restricting its performance.
[0003] In order to overcome these shortcomings, researchers have explored various nanostructure designs, including WS2 nanowires, WS2 nanosheets, WS2 nanoflowers, WS2 nanofibers, etc. as negative electrode materials for sodium ion battery systems (ElectrochimicaActa.302.259(2019)). Although the sodium storage capacity of tungsten disulfide has been improved to a certain extent, its long-term cycle stability is still poor due to its insufficient structural strength. Graphene, as a flexible carbon material with good electrical properties and high chemical stability, is often combined with other transition metal sulfides to form various high-performance composite materials and used as electrode materials for various energy storage systems (Energy Storage Materials.24.22(2020)), but there are few studies on graphene and tungsten disulfide composite materials and the sodium storage capacity of the reported composite materials can still be improved (Advanced Energy Materials.6.1601057(2016)). It is still a challenge to achieve excellent synergistic effects between tungsten disulfide and graphene and improve their sodium storage capacity with excellent structural design. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a tungsten disulfide / graphene composite material. Tungsten salt is deposited on the surface of a silicon ball modified with graphene oxide, and a tungsten disulfide / graphene composite material is obtained after a high-temperature sulfurization reaction and sequentially treated with an alkaline solution and an acid solution. The preparation method of the material has the characteristics of simple operation and easy mass preparation. The prepared tungsten disulfide / graphene composite material has a three-dimensional multi-level porous structure and exhibits excellent electrochemical properties as a negative electrode material for sodium ion batteries.
[0005] In order to achieve the above purpose, the technical solution of the present invention is as follows:
[0006] In one aspect, the present invention provides a method for preparing a tungsten disulfide / graphene composite material, comprising the following steps:
[0007] (1) using 3-aminopropyltrimethoxysilane to modify the surface of a silicon sphere alcohol dispersion by a constant temperature reflux method under an inert atmosphere to obtain silicon spheres with surface functional groups modified, and ultrasonically dispersing the silicon spheres with surface functional groups modified and graphene oxide in an alcohol solution, stirring, and obtaining a graphene oxide / silicon sphere composite;
[0008] (2) depositing tungsten salt on the graphene oxide / silicon sphere composite obtained in step (1) by a coprecipitation method to obtain a precursor mixture;
[0009] (3) transferring the precursor mixture and the sulfur source obtained in step (2) into a high-temperature reaction vessel under an inert atmosphere;
[0010] (4) placing the high temperature reaction kettle in step (3) in a muffle furnace, heating the temperature to a terminal temperature of 300 to 600° C. by program, and then maintaining the temperature;
[0011] (5) treating the product obtained in step (4) with alkali, washing, and drying to obtain a silicon ball / tungsten disulfide / graphene composite material;
[0012] (6) treating the product obtained in step (5) with acid, washing, and drying to obtain a tungsten disulfide / graphene composite material.
[0013] Furthermore, in the step (1), the diameter of the silicon spheres in the silicon sphere alcohol dispersion is 20 to 400 nm; the inert atmosphere is one or a mixture of argon, nitrogen, and helium; the reflux temperature is 50 to 200° C.; and the stirring time is 1 to 48 hours.
[0014] Furthermore, in the step (2), the tungsten salt is any one of ammonium tungstate, ammonium metatungstate, ammonium tetrathiotungstate, sodium metatungstate or sodium tungstate; the coprecipitation temperature is 25-100°C, and the time is 6-72h.
[0015] Furthermore, in step (3), the second inert atmosphere is one of argon, nitrogen, and helium, or a mixture of several of them; the sulfur source is any one of carbon disulfide, sodium sulfide, potassium sulfide, ammonium sulfide, and thioacetamide; and the mass ratio of tungsten salt to sulfur source is 1:0.5-2.
[0016] Furthermore, in the step (4), the programmed temperature treatment is carried out by heating the temperature at a rate of 1 to 20°C / min to the end temperature, and the constant temperature time is 2 to 6 hours.
[0017] Furthermore, in the step (5), the alkali in the alkali treatment is a sodium hydroxide solution with a concentration of 1 to 8 mol / L or a potassium hydroxide solution with a concentration of 1 to 8 mol / L, the alkali treatment time is 2 to 6 hours, the alkali treatment temperature is 60 to 100° C.; the drying temperature is 25 to 80° C., and the drying time is 4 to 48 hours.
[0018] Furthermore, in the step (6), the acid in the acid treatment is a hydrofluoric acid solution with a concentration of 5 to 20%, and the acid treatment time is 4 to 48 hours; the drying temperature is 25 to 80° C., and the drying time is 4 to 48 hours.
[0019] Another aspect of the present invention provides a tungsten disulfide / graphene composite material obtained by the above preparation method, wherein the tungsten disulfide / graphene composite material has a three-dimensional multi-level porous structure.
[0020] The present invention also provides an application of the tungsten disulfide / graphene composite material, wherein the composite material is used as a negative electrode material in a sodium ion battery system.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The tungsten disulfide / graphene composite material of the present invention has a three-dimensional multi-level pore structure. When used as a negative electrode material for a sodium ion battery, it ensures sufficient contact between the electrode material and the electrolyte, shortens the diffusion path of ions, and improves the sodium storage capacity of the material. The introduction of graphene improves the conductivity of the material while also enhancing the cycle stability of the material in long-term charge and discharge tests.
[0023] 2. The present invention directly obtains tungsten disulfide / graphene composite materials through high-temperature autoclave reaction without the need for additional calcination and carbonization processes, and the preparation process is simple.
[0024] 3. The method of the present invention can be prepared in large quantities and has a wide range of applications. The obtained tungsten disulfide / graphene composite material has potential application prospects in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The N2 adsorption-desorption isotherms and pore size distribution diagrams of the tungsten disulfide / graphene composite material and the tungsten disulfide material in Example 1 and Comparative Example 1;
[0026] Figure 2 is a high resolution scanning electron microscope (HRSEM) image of the tungsten disulfide / graphene composite material in Example 1;
[0027] Figure 3 It is a high resolution scanning electron microscope (HRSEM) image of the tungsten disulfide material in Comparative Example 1;
[0028] Figure 4It is a high resolution scanning electron microscope (HRSEM) image of the graphene material in Comparative Example 2;
[0029] Figure 5 The tungsten disulfide / graphene composite material in Example 1 is tested in the voltage range of 0.01 to 3 V and the current density of 100 mA·g -1 Performance diagram when
[0030] Figure 6 The tungsten disulfide / graphene composite material in Example 1 is tested in the voltage range of 0.01 to 3 V and the current density of 2000 mA·g -1 Performance diagram when
[0031] Figure 7 The tungsten disulfide / graphene composite material in Example 2 is tested in the voltage range of 0.01 to 3 V and the current density of 2000 mA·g -1 Performance diagram when
[0032] Figure 8 The tungsten disulfide / graphene composite material in Example 2 is tested in the voltage range of 0.01 to 3 V and the current density of 100 mA·g -1 Performance diagram when
[0033] Fig. 9 The tungsten disulfide material in Comparative Example 1 was tested in a voltage range of 0.01 to 3 V and a current density of 100 mA·g -1 Performance diagram when
[0034] Fig.10 The graphene material in Comparative Example 2 was tested in a voltage range of 0.01 to 3 V and a current density of 100 mA·g -1 Performance graph when . DETAILED DESCRIPTION
[0035] The whole material preparation process is described in detail below through examples.
[0036] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0037] (1) adding silicon spheres to ethanol, ultrasonically dispersing for 30 to 45 minutes to obtain a silicon sphere ethanol dispersion, adding 3-aminopropyltrimethoxysilane, refluxing at a constant temperature of 50 to 200° C. under an inert atmosphere, cooling to room temperature after reflux, centrifuging and washing to obtain silicon spheres modified with surface functional groups, ultrasonically dispersing the silicon spheres modified with surface functional groups and graphene oxide in ethanol for 30 to 45 minutes, stirring at room temperature for 1 to 48 hours, and centrifuging and washing to obtain a graphene oxide / silicon sphere composite;
[0038] (2) dissolving and dispersing the tungsten salt and the graphene oxide / silicon sphere composite obtained in step (1) in deionized water, stirring at 25 to 100° C. for 6 to 72 hours until the solvent is completely evaporated, and then transferring to an oven for drying to obtain a precursor mixture;
[0039] (3) under the protection of an inert atmosphere, transferring the precursor mixture obtained in step (2) and the sulfur source into a high-temperature reaction kettle and sealing the reaction kettle;
[0040] (4) placing the reactor in step (3) in a muffle furnace, heating the reactor to 300-600° C., and maintaining the temperature for 2-6 hours;
[0041] (5) treating the sample obtained in step (4) with an alkali solution at a temperature of 60 to 100° C. for a time of 2 to 6 h, filtering with suction, washing with water and ethanol multiple times until the filtrate is neutral, and drying at 25 to 80° C. for 4 to 48 h;
[0042] (6) Treat the sample obtained in step (5) with an acid solution for 4 to 48 hours to remove the silicon balls, filter it, wash it with water and ethanol several times until the filtrate is neutral, and dry it at 25 to 80° C. for 4 to 48 hours to obtain a tungsten disulfide / graphene composite material with a three-dimensional multi-level porous structure.
[0043] In step (1), the inert atmosphere is preferably high-purity argon; the reflux temperature is preferably 100-120° C.; and the stirring time is preferably 12-24 h.
[0044] In step (2), the drying temperature is preferably 60-80°C.
[0045] In step (3), the second inert atmosphere is preferably high-purity argon.
[0046] In step (4), the programmed heating rate is preferably 10-15°C / min; the preferred end point temperature is 400°C, and the preferred constant temperature time is 4h.
[0047] In step (5), the alkaline solution is preferably a 4-6 mol / L NaOH solution; the alkaline treatment temperature is preferably 60° C., and the treatment time is preferably 3 h.
[0048] In step (6), the acid solution is preferably a hydrofluoric acid solution with a mass fraction of 10%, and the acid treatment time is preferably 12 hours.
[0049] Example 1
[0050] (1) 1.6 g of silicon spheres with a diameter of 100 nm were ultrasonically dispersed in 200 mL of ethanol, and 4 mL of 3-aminopropyltrimethoxysilane was added under an argon atmosphere. The mixture was refluxed at 120° C. for 5 h. After the reflux, the mixture was cooled to room temperature, centrifuged, washed, and ultrasonically dispersed with 150 mg of graphene oxide in 200 mL of ethanol. The mixture was stirred at room temperature for 12 h and then centrifuged and washed to obtain a graphene oxide / silicon sphere composite.
[0051] (2) 300 mg of sodium tungstate and graphene oxide / silicon sphere composite were ultrasonically dispersed in 50 mL of deionized water, stirred at room temperature until the solvent was completely evaporated, and transferred to an oven and dried at 80° C. for 8 h to obtain a precursor mixture;
[0052] (3) The precursor mixture and 10 mL of CS2 were sealed in a high-temperature reaction vessel under an argon atmosphere;
[0053] (4) The high temperature reactor was transferred to a muffle furnace, and the temperature was raised to 400 °C at a heating rate of 10 °C / min and kept at this temperature for 4 h;
[0054] (5) treating the sample obtained in step (4) with a 6 mol / L sodium hydroxide solution at a temperature of 60° C. for 3 h. After the treatment, filtering with suction, washing with water and ethanol several times until the filtrate is neutral, and then drying in a forced air drying oven at 80° C. for 12 h.
[0055] (6) The sample obtained in step (5) is treated with a 10% by mass hydrofluoric acid solution for 12 hours. After the treatment, the sample is filtered and washed with water and ethanol several times until the filtrate is neutral. The washed sample is placed in a forced air drying oven and dried at 80° C. for 12 hours to obtain a tungsten disulfide / graphene composite material.
[0056] N2 adsorption and desorption experiments (see Figure 1 ) shows that the obtained tungsten disulfide / graphene composite material has pores of different sizes, and the high-resolution scanning electron microscope image (see Figure 2 ) also shows that the material has three-dimensional multi-level porous structure characteristics.
[0057] Example 2
[0058] (1) 1.6 g of silicon spheres with a diameter of 100 nm were ultrasonically dispersed in 200 mL of ethanol, 4 mL of 3-aminopropyltrimethoxysilane was added under argon atmosphere, and refluxed at 120° C. for 5 h. After reflux, the mixture was cooled to room temperature, centrifuged, washed, and ultrasonically dispersed with 150 mg of graphene oxide in 200 mL of ethanol. The mixture was stirred at room temperature for 12 h and then centrifuged and washed to obtain a graphene oxide / silicon sphere composite;
[0059] (2) 150 mg of sodium tungstate and graphene oxide / silicon sphere composite were ultrasonically dispersed in 50 mL of deionized water, stirred at room temperature until the solvent was completely evaporated, and then transferred to an oven and dried at 80° C. for 8 h to obtain a precursor mixture;
[0060] (3) The precursor mixture and 10 mL CS2 were sealed in a high temperature reaction vessel under an argon atmosphere;
[0061] (4) The high temperature reactor was transferred to a muffle furnace, and the temperature was raised to 400 °C at a heating rate of 10 °C / min and kept at this temperature for 4 h;
[0062] (5) treating the sample obtained in step (4) with a 6 mol / L sodium hydroxide solution at a temperature of 60° C. for 3 h. After the treatment, filtering with suction, washing with water and ethanol several times until the filtrate is neutral, and then drying in a forced air drying oven at 80° C. for 12 h.
[0063] (6) The sample obtained in step (5) is treated with a 10% by mass hydrofluoric acid solution for 12 hours. After the treatment, the sample is filtered and washed with water and ethanol several times until the filtrate is neutral. The washed sample is placed in a forced air drying oven and dried at 80° C. for 12 hours to obtain a tungsten disulfide / graphene composite material.
[0064] Comparative Example 1
[0065] (1) 1.6 g of silicon spheres with a diameter of 100 nm and 300 mg of sodium tungstate were ultrasonically dispersed and dissolved in 50 mL of deionized water, stirred at room temperature until the solvent was completely evaporated, and then transferred to an oven and dried at 80°C for 8 h;
[0066] (2) The sample in (1) was sealed in a high temperature reactor under an argon atmosphere and the high temperature reactor was transferred to a muffle furnace. The temperature was raised to 400°C at a heating rate of 10°C / min and kept constant for 4 h.
[0067] (3) treating the sample obtained in (2) with a 6 mol / L sodium hydroxide solution at 60° C. for 3 h. After the treatment, filtering was performed and washing was performed with water and ethanol for multiple times until the filtrate was neutral.
[0068] (4) treating the sample obtained in (3) with a 10% hydrofluoric acid solution for 12 h. After the treatment, filtering, washing with water and ethanol several times until the filtrate is neutral, and then drying in a forced air drying oven at 80° C. for 12 h.
[0069] (5) The sample washed in (4) is placed in a forced air drying oven and dried at 80° C. for 12 h to obtain tungsten disulfide material.
[0070] N2 adsorption and desorption experiments (see Figure 1) shows that the material also has different pore size distribution. High resolution scanning electron microscopy (see Figure 3 ) shows that the material also has the characteristics of a three-dimensional multi-level porous structure, but because graphene is not introduced, the structure is more regular.
[0071] Comparative Example 2
[0072] (1) 1.6 g of silicon spheres with a diameter of 100 nm were ultrasonically dispersed in 200 mL of ethanol. Under an argon atmosphere, 4 mL of 3-aminopropyltrimethoxysilane was added and refluxed at 120° C. for 5 h. After the reflux was completed, the spheres were cooled to room temperature, centrifuged, washed, and ultrasonically dispersed with 150 mg of graphene oxide in 200 mL of ethanol. After stirring at room temperature for 12 h, the spheres were centrifuged and washed, and then transferred to an oven and dried at 80° C. for 8 h.
[0073] (2) The sample in step (1) and 10 mL of CS2 were sealed in a high-temperature reaction kettle under an argon atmosphere, and the high-temperature reaction kettle was transferred to a muffle furnace, and the temperature was raised to 400° C. at a heating rate of 10° C. / min and kept at this temperature for 4 h;
[0074] (3) treating the sample obtained in step (2) with a 6 mol / L sodium hydroxide solution at a temperature of 60° C. for 3 h. After the treatment, filtering with suction, and washing with water and ethanol multiple times until the filtrate is neutral;
[0075] (4) treating the sample obtained in step (3) with a 10% hydrofluoric acid solution for 12 h. After the treatment, filtering, washing with water and ethanol several times until the filtrate is neutral, and then drying in a forced air drying oven at 80° C. for 12 h.
[0076] (5) The sample washed in step (4) was placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a graphene material.
[0077] High resolution scanning electron microscopy (see Figure 4 ) shows that the material has no obvious porous structure.
[0078] Application Example 1
[0079] The tungsten disulfide / graphene composite material obtained in Example 1 was applied to a sodium ion battery system to examine its electrochemical performance when used as a negative electrode material of the battery.
[0080] 1.Battery preparation:
[0081] Active material, acetylene black and binder (PVDF) were weighed in a mass ratio of 7:2:1 in a suitable amount of 1-methyl-2-pyrrolidone to form a uniform active material slurry. The active material slurry was coated on a copper foil using a coating machine, and then placed in an oven at 60°C for 24 hours. In an argon-filled glove box (to ensure that the water and oxygen values were all below 0.1ppm), metallic sodium was used as the counter electrode, Whatman glass fiber was used as the diaphragm, and 1.0M NaPF6 was dissolved in 5wt% fluoroethylene carbonate, ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 and used as the electrolyte to assemble a CR2032 battery.
[0082] 2.Electrochemical performance evaluation:
[0083] Test conditions:
[0084] Temperature: 30°C; Voltage range: 0.01-3V; Current density: 100mA·g -1 and 2000mA g -1 .
[0085] 3. Results and Discussion
[0086] At 100mA g -1 At a current density of 1.34 W / m3 / g, the first cycle charge and discharge capacity of the tungsten disulfide / graphene composite material was 1214 mAh g -1 and 469mAh·g -1 After 100 cycles of charge and discharge tests, the material still maintained a capacity of 419 mAh g -1 The reversible specific capacity (see Figure 5 ). At 2000mA g -1 At a current density of 1000, the battery still has a high capacity of 244 mAh g -1 The specific capacity (see Figure 6 ).
[0087] Application Example 2
[0088] The tungsten disulfide / graphene composite material obtained in Example 2 was applied to a sodium ion battery system to examine its electrochemical performance when used as a negative electrode material of the battery.
[0089] 1.Battery preparation:
[0090] Active material, acetylene black and binder (PVDF) were weighed in a mass ratio of 7:2:1 in a suitable amount of 1-methyl-2-pyrrolidone to form a uniform active material slurry. The active material slurry was coated on a copper foil using a coating machine, and then placed in an oven at 60°C for 24 hours. In an argon-filled glove box (to ensure that the water and oxygen values were all below 0.1ppm), metallic sodium was used as the counter electrode, Whatman glass fiber was used as the diaphragm, and 1.0M NaPF6 was dissolved in 5wt% fluoroethylene carbonate, ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 and used as the electrolyte to assemble a CR2032 battery.
[0091] 2.Electrochemical performance evaluation:
[0092] Test conditions:
[0093] Temperature: 30°C; Voltage range: 0.01-3V; Current density: 100mA·g -1 and 2000mA·g -1 .
[0094] 3. Results and Discussion
[0095] The tungsten disulfide / graphene composite material can withstand high currents of 2000 mA g -1 After 1000 cycles of charge and discharge tests, the battery capacity remained at 152 mAh g -1 The reversible specific capacity (see Figure 7 ), compared with the material performance data in Application Example 1 (244 mAh g -1 ) is low, at a current density of 100 mA g -1 The material can be charged and discharged for 100 times to obtain 318 mAh g -1 The specific capacity ( Figure 8 ), which is also lower than 419 mAh g in Application Example 1. -1 The reversible specific capacity of the material can be reduced to a certain extent by reducing the proportion of tungstate in the raw material.
[0096] Application Example 3
[0097] The tungsten disulfide material obtained in Comparative Example 1 was applied to a sodium ion battery system to examine its electrochemical performance when used as a negative electrode material of the battery.
[0098] 1.Battery preparation:
[0099] Active material, acetylene black and binder (PVDF) were weighed in a mass ratio of 7:2:1 in a suitable amount of 1-methyl-2-pyrrolidone to form a uniform active material slurry. The active material slurry was coated on a copper foil using a coating machine, and then placed in an oven at 60°C for 24 hours. In an argon-filled glove box (to ensure that the water and oxygen values were all below 0.1ppm), metallic sodium was used as the counter electrode, Whatman glass fiber was used as the diaphragm, and 1.0M NaPF6 was dissolved in 5wt% fluoroethylene carbonate, ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 and used as the electrolyte to assemble a CR2032 battery.
[0100] 2.Electrochemical performance evaluation:
[0101] Test conditions:
[0102] Temperature: 30°C; Voltage range: 0.01-3V; Current density: 100mA·g -1 .
[0103] 3. Results and Discussion
[0104] The tungsten disulfide material is -1 The test showed very poor cycle stability and the specific capacity after 100 cycles of charge and discharge test was 41 mAh g -1 ( Fig. 9 ), which is much lower than the performance of the tungsten disulfide and graphene composite materials in Application Example 1 and Application Example 2, which shows that the excellent composite of tungsten disulfide and graphene can improve the performance of the material.
[0105] Application Example 4
[0106] The graphene material obtained in Comparative Example 2 was applied to a sodium ion battery system to examine its electrochemical performance when used as a negative electrode material of the battery.
[0107] 1.Battery preparation:
[0108] Active material, acetylene black and binder (PVDF) were weighed in a mass ratio of 7:2:1 in a suitable amount of 1-methyl-2-pyrrolidone to form a uniform active material slurry. The active material slurry was coated on a copper foil using a coating machine, and then placed in an oven at 60°C for 24 hours. In an argon-filled glove box (to ensure that the water and oxygen values were all below 0.1ppm), metallic sodium was used as the counter electrode, Whatman glass fiber was used as the diaphragm, and 1.0M NaPF6 was dissolved in 5wt% fluoroethylene carbonate, ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 and used as the electrolyte to assemble a CR2032 battery.
[0109] 2.Electrochemical performance evaluation:
[0110] Test conditions:
[0111] Temperature: 30°C; Voltage range: 0.01-3V; Current density: 100mA·g -1 .
[0112] 3. Results and Discussion
[0113] The graphene material is subjected to a current density of 100 mA g -1 The specific capacity after 100 cycles of charge and discharge tests is 176 mAh g -1 ( Fig.10 ), and its comprehensive performance with that of Application Example 3 is much lower than 419 mAh·g in Application Example 1. -1 The reversible specific capacity and 318 mAh g in Application Example 2 -1 The above results show that the performance of the excellent composite of tungsten disulfide and graphene is far better than that of tungsten disulfide or graphene alone.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a tungsten disulfide / graphene composite material, characterized in that: The following steps are involved: (1) using 3-aminopropyltrimethoxysilane to modify the surface of a silicon sphere ethanol dispersion by a constant temperature reflux method under an inert atmosphere to obtain silicon spheres with surface functional groups modified, and ultrasonically dispersing the silicon spheres with surface functional groups modified and graphene oxide in an ethanol solution, and stirring to obtain a graphene oxide / silicon sphere composite; (2) depositing tungsten salt on the graphene oxide / silicon sphere composite obtained in step (1) by a coprecipitation method to obtain a precursor mixture; (3) transferring the precursor mixture and the sulfur source obtained in step (2) into a high-temperature reaction vessel under an inert atmosphere; (4) placing the high temperature reaction kettle in step (3) in a muffle furnace, heating the temperature to a terminal temperature of 300 to 600° C. by program, and then maintaining the temperature; (5) treating the product obtained in step (4) with alkali, washing, and drying to obtain a silicon ball / tungsten disulfide / graphene composite material; (6) treating the product obtained in step (5) with acid, washing, and drying to obtain a tungsten disulfide / graphene composite material.
2. The preparation method according to claim 1, characterized in that: In the step (1), the diameter of the silicon spheres in the silicon sphere alcohol dispersion is 20 to 400 nm; the inert atmosphere is one or a mixture of argon, nitrogen, and helium; the reflux temperature is 50 to 200° C.; and the stirring time is 1 to 48 hours.
3. The preparation method according to claim 1, characterized in that: In the step (2), the tungsten salt is any one of ammonium tungstate, ammonium metatungstate, ammonium tetrathiotungstate, sodium metatungstate or sodium tungstate; the coprecipitation temperature is 25-100°C and the time is 6-72h.
4. The preparation method according to claim 1, characterized in that: In the step (3), the second inert atmosphere is one of argon, nitrogen, and helium, or a mixture of several of them; the sulfur source is any one of carbon disulfide, sodium sulfide, potassium sulfide, ammonium sulfide, and thioacetamide; and the mass ratio of tungsten salt to sulfur source is 1:0.5-2.
5. The preparation method according to claim 1, characterized in that: In the step (4), the programmed temperature treatment is performed by heating the temperature at a rate of 1 to 20°C / min to the end temperature, and the constant temperature time is 2 to 6 hours.
6. The preparation method according to claim 1, characterized in that: In the step (5), the alkali in the alkali treatment is a sodium hydroxide solution with a concentration of 1 to 8 mol / L or a potassium hydroxide solution with a concentration of 1 to 8 mol / L, the alkali treatment time is 2 to 6 hours, the alkali treatment temperature is 60 to 100° C.; the drying temperature is 25 to 80° C., and the drying time is 4 to 48 hours.
7. The preparation method according to claim 1, characterized in that: In the step (6), the acid in the acid treatment is a hydrofluoric acid solution with a mass fraction of 5 to 20%, and the acid treatment time is 4 to 48 hours; the drying temperature is 25 to 80° C., and the drying time is 4 to 48 hours.
8. A tungsten disulfide / graphene composite material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The tungsten disulfide / graphene composite material has a three-dimensional multi-level pore structure.
9. An application of the tungsten disulfide / graphene composite material according to claim 8, characterized in that: The composite material is used as a negative electrode material in a sodium ion battery system.
Citation Information
Patent Citations
Preparation method for tungsten disulfide / carbon nanotube negative electrode composite material of sodium ion battery
CN105870417A
Three-dimensional macroporous tungsten disulfide / carbon composite material and preparation method and application thereof
CN114628673A